Use numbers not words! Communicating hotels’ cleaning programs for COVID-19 from the brand perspective - Jiménez-Barreto, J.; Loureiro, S. M. C.; Braun, E.; Sthapit, E.; Zenker, S. (International Journal of Hospitality Management, 2021)
After hotels in many countries were forced to close in government-imposed lockdowns during the COVID-19 pandemic, there is an inherent need to communicate how they deal with the coronavirus to motivate guests to visit. However, lack of knowledge about how to persuasively communicate about hotels’ cleaning programs for COVID-19 can challenge the industry’s survival. We investigated how hotels that position their brand as a particular personality (sincere vs. exciting) could benefit from different communication styles (inclusion of numerical vs. verbal quantifiers) when presenting their COVID-19 cleaning procedures. Study 1 explored tourists’ central attitudinal responses toward hotels’ cleaning programs. Study 2 demonstrated that sincere hotel brands would benefit from using numerical and verbal quantifiers to communicate their cleaning policies, whereas exciting hotel brands would benefit only from numerical quantifiers. Our results invite hotel managers to use their brand personality positioning to influence tourists’ attitudes and intentions in a pandemic context.